2019
DOI: 10.1021/acs.jafc.8b06347
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Encapsulation within Oil-in-Water Emulsions: Impact of Emulsifier Type on Physicochemical Stability and Bioaccessibility

Abstract: The influence of plant-based (gum arabic and quillaja saponin) and animal-based (whey protein isolate, WPI) emulsifiers on the production and stability of vitamin E-fortified emulsions was investigated. Their impact on lipid digestibility and vitamin bioaccessibility was also studied utilizing an in vitro gastrointestinal tract. WPI and saponin produced smaller emulsions than gum arabic. All emulsions had good storage stability at room temperature (4 weeks, pH 7). Saponin-and gum arabic-emulsions were resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 53 publications
4
46
0
Order By: Relevance
“…The oil droplets in emulsion-based delivery systems may be coated by various kinds of natural or synthetic emulsifiers, such as proteins, polysaccharides, phospholipids, saponins, and small-molecule surfactants [20,21]. In vitro digestion studies have shown that the nature of the emulsifier-coating oil droplets can have a pronounced effect on the bioavailability of encapsulated hydrophobic bioactives [107][108][109][110]. This phenomenon may be due to a number of factors.…”
Section: Emulsifier Typementioning
confidence: 99%
“…The oil droplets in emulsion-based delivery systems may be coated by various kinds of natural or synthetic emulsifiers, such as proteins, polysaccharides, phospholipids, saponins, and small-molecule surfactants [20,21]. In vitro digestion studies have shown that the nature of the emulsifier-coating oil droplets can have a pronounced effect on the bioavailability of encapsulated hydrophobic bioactives [107][108][109][110]. This phenomenon may be due to a number of factors.…”
Section: Emulsifier Typementioning
confidence: 99%
“…Liquid chromatography is another common method to assess the chemical stability of lipid-soluble bioactives encapsulated in nanoemulsions, such as β-carotene [ 57 ], lycopene [ 58 ], vitamin E [ 59 ] and vitamin A [ 60 ].…”
Section: Nanoemulsion Technologymentioning
confidence: 99%
“…In addition, vitamin E easily degrades when exposed to oxygen, heat and light. Thus, its encapsulation in nanoemulsions facilitates its incorporation in food products [ 59 ].…”
Section: Encapsulation Of Lipid-soluble Bioactive Compounds By Nanmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipophilic bioactive compounds, such as α-toc, are usually situated inside of the lipid droplets and, in order to be released, the surrounding TGs have to be digested. After being released from the droplets, they have to be incorporated into the hydrophobic areas within the mixed micelles; if not, they will precipitate or form a separate layer [43]. To assess the suitability of Ec_AG, E10W, E10UW and E20UW as emulsion-based delivery systems for lipophilic compounds, presence of α-toc in the oil phase were examined after in vitro oral, gastric and intestinal digestion (Figure 2).…”
Section: Effect Of In Vitro Digestion On α-Toc Stabilitymentioning
confidence: 99%